STIMULASI SPASIAL-VISUAL DENGAN BUILDING SIMULATOR GAME ANAK USIA 5 TAHUN - Mahkamah Brantasari (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
AbstractGame play at this time can no longer be avoided, both by adults and children, the reasons for playing games are diverse ranging from filling spare time to eliminate the boredom experienced by humans at different age levels. So that game play does not only end with activities that are not useful, then as an adult must direct that the game play can be useful and used as a stimulating tool for children and can improve children's spatial-visual intelligence. This research was conducted on a child who is five years old, by conducting research using a game on a smartphone, the Building Simulator Game, which is specialized in Block Craft 3D level 1. The activity carried out is collecting data by exploring the ability of children in game play, doing observation and directly involved in directing children to play games. In stimulating spatial-visual intelligence with Building Simulator Games there are a number of children aged 5 years. First: determine the simplest building simulator game, Second: introduce block-shaped block media, Third: choose the type of building to be made, Fourth: Block Craft 3 D consists of level 26, but researchers only introduce children to level 1 according to their abilities. With the Block Craft 3 D game, it is expected that spatial-visual stimulation will be beneficial for children in the future